Entangled Histories: German Veterinary Medicine, c.1770–1900 - Mitsuda, Tatsuya (Med Hist, 2017)
Medical historians have recently become interested in the veterinary past, investigating the development of animal health in countries such as France, the Netherlands, the United Kingdom and the United States. An appreciation of the German context, however, is still lacking – a gap in the knowledge that the present article seeks to fill. Providing a critical interpretation of the evolution of the veterinary profession, this investigation explains why veterinary and medical spheres intersected, drifted apart, then came back together; it also accounts for the stark differences in the position of veterinarians in Germany and Britain. Emphasis is placed on how diverse traditions, interests and conceptualisations of animal health shaped the German veterinary profession, conditioned its field of operation, influenced its choice of animals and diseases, and dictated the speed of reform. Due to a state-oriented model of professionalisation, veterinarians became more enthusiastic about public service than private practice, perceiving themselves to be alongside doctors and scientists in status, rather than next to animal healers or manual labourers. Building on their expertise in epizootics, veterinarians became involved in zoonoses, following outbreaks of trichinosis. They achieved a dominant position in meat hygiene by refashioning abattoirs into sites for the construction of veterinary knowledge. Later, bovine tuberculosis helped veterinarians cement this position, successfully showcasing their expertise and contribution to society by saving as much meat as possible from diseased livestock. Ultimately, this article shows how veterinarians were heavily ‘entangled’ with the fields of medicine, food, agriculture and the military.